Technological proposal for the implementation of a 4.5 kwp photovoltaic plant for the rural community altoandina San Francisco de Raymina, Ayacucho-Peru - Salvador Tixe, Carlos Alberto (2021)
This document is part of a research work, where the energetic situation of the rural community San Francisco de Raymina, located in the Ayacucho Region at 3798 masl, is evaluated.  The current situation of electric energy supply in the locality is described and analyzed.  Based on a situational diagnosis, identifying the needs (use and consumption) of electric energy of the population, and an evaluation of the renewable energy potential of the place, a clean and viable technological solution is proposed. Particularly, as the community has very limited electricity supply, typical for many similar villages, insufficient for the development of productive activities, a local photovoltaic installation is proposed, in order to replace the conventional grid system and to satisfy the local demand in a sustainable way.